PLACE AND CHARACTERISTICS OF THE HEAD OF THE TERRITORIAL AUTHORITY OF THE NATIONAL POLICE IN THE SYSTEM OF SUBJECTS OF CONTROL (Bulletin of criminological association of Ukraine, 2024)
The scientific work proved that the head of the territorial body of the National Police is an important structural element of the system of subjects of control of the National Police of Ukraine. It is responsible for the performance of management functions, the organization of combating crime in the assigned territory, ensuring public order and security in the territory of service, establishing relations with the public and representatives of local self-government, for cooperation and interaction on the basis of partnership, and many other areas and directions control, which make the position of the head of the territorial unit of the National Police of Ukraine significant and important in the system of subjects of police control. It was emphasized that the head of this unit must possess the skills of constant self-improvement and adaptation to a dynamic, changing situation, must have tactical and strategic thinking in order to organize the work of the unit properly and foresee possible crisis situations. Openness, the ability to establish interaction with subordinate personnel on a democratic basis, intolerance to authoritarian models of behavior and personnel management must be close and inherent to the head of a territorial unit of a modern formation. It is argued that only an experienced and comprehensively developed person can hold such a responsible position as the head of the territorial unit of the National Police of Ukraine, since the main countermeasures against crime in the country are carried out by the efforts of the personnel of these institutions, and on their shoulders lies the shaft of revealing the largest number of criminal offenses and conducting pre-trial investigations according to them Employees of territorial divisions of the National Police of Ukraine are the closest to the population and the first link of interaction that protects the rights of citizens, their safety, life and health, that is why it is critically important that the work of these police institutions be organized accordingly. As a conclusion, the head of police units of the above-mentioned type is an important component and structural unit of the control system of the National Police of Ukraine, and the success of the police work in general, the protection of the rights and freedoms of citizens, as well as their lives and health depends on the effectiveness of his activities.
Keywords: manager; territorial unit; National Police of Ukraine; discipline; legality; subordinate personnel; police officer; control; subjects of control